Citizen's Perception About Public Administration Reforms in Romania - Dan Sorin ȘANDOR; Ciprian Raul TRIPON (Transylvanian Review of Administrative Sciences, 2008)
The present paper tries to assess the publicadministration reforms based on the opinionsof the citizens – the ones supposed to be thebeneficiaries of these measures. The paper hastwo main parts, the first one being a theoreticaldescription of the factors and causes that influencereform processes, with a special emphasis on thefeed-back impact generated by the perception ofthe results of the reform and the second one beinga presentation of empirical data concerning theRomanian citizens’ perceptions about the reformin the public sector.Data comes from a national survey doneby the Public Administration Department inDecember 2007.The main findings show us thatcitizens agree with the need for reforms but theresults are not those expected. In their opinion thereform had lost its initial goal, that of improvingthe functioning of PA in order to provide betterservices for citizens.